Field Evaluation of the Ultrasonic Personal Aerosol Sampler (UPAS) for Respirable Dust Exposure in a Taconite Mine. - Afshar-Mohajer, Nima; Foos, Rebecca; Ramachandran, Gurumurthy; Volckens, John (Annals of Work Exposures & Health, 2021)
Exposure to respirable dust (RD; the mass fraction of inhaled particles that penetrate to the unciliated airways) is a major health concern in a variety of workplaces. While the estimation of personal exposure is an essential step in protecting worker health from aerosol hazards, the traditional method for assessing personal exposure to RD, suggested by the National Institute for Occupational Safety and Health (NIOSH method 0600), requires equipment that is heavy, bulky, noisy, and has the need of frequent calibration. The ultrasonic personal aerosol sampler (UPAS) is a new personal sampling technology designed to address some of these drawbacks associated with traditional sampling methods. In this study, we field tested and evaluated the performance of the UPAS for assessing worker exposure to RD in a taconite mine. Mineworkers (n = 39) from various job categories were recruited to wear both UPAS and NIOSH 0600 samplers on a work vest to estimate time-weighted exposure to RD. A strong linear relationship was observed (NIOSH method 0600 = 1.06 (UPAS) −9.22 µg m–3, r 2 of 0.72, and Pearson correlation coefficient of 0.854). None of the workers were exposed to a RD concentration above the Occupational Safety and Health Administration permissible exposure limit (5 mg m–3). A Bland–Altman analysis revealed that 72% of the valid UPAS samples agreed within ±25% of the traditional method mean. The impact of job category on the correlation of the methods was not statistically significant. This work suggests that the UPAS may present a viable alternative for assessing personal exposure to RD in the workplace.